ELIMINASI RISIKO OPERASIONAL BMT SRI SEJAHTERA SURABAYA - Yanuar Dharma Putra; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The results of this research are risk mitigation measures in the continuity of internal processes, human resources, technology and information. Risk mitigation on the internal processes is done by performing supervision based on employees job description, and implementation of sharia financing agreements with customers. Risk mitigation on human resources is done by providing moral guidance to employees. Risk mitigation in information technology is carried out by performing regular maintenance of computer software and hardware, as well as other devices that support Baitul Maal wa tamwil Sri Sejahtera business activities.  REFFERENCESAlexander, Carol. 2003. Operational Risk: Regulation, Analysis and Management. London: Prentice HallAlijoyo, Antonious. 2006. Enterprise Risk Management: Pendekatan Praktis. Edisikedua. Jakarta: PT. Ray IndonesiaChapra, M. Umer. 2000. Islam dan Tantangan Ekonomi. Jakarta: Gema Insani Press dan Tazkia InstituteDjohanputro. Bramantyo. 2006. Prinsip-Prinsip Ekonomi Makro. Cetakan 1. Jakarta: PPMFrame. J. Davidson. 2003. Managing Risk in Organisations: A Guide for Managers. San Francisco. Jossey Bass: A wiley imprintHerman, Darmawi. 2008. Manajemen Risiko. Jakarta: Bumi AksaraIlmi, Makhalul. 2002. Teori dan Praktek Lembaga Mikro Keuangan Syariah: Beberapa Permasalahan dan Alternatif Solusi. Yogyakarta: UII PressKarim, Adiwarman Azwar. 2006. Bank Islam: Analisis Fiqih dan Keuangan. Jakarta: PT. Raja Grafindo PersadaKhan, Tariqullah and Habis Ahmed. 2008. Manajemen Risiko Lembaga Keuangan Syariah. Jakarta: Bumi AksaraMamduh, M. Hanafi. 2009. Manajemen RIsiko. Yogyakarta: UPP STI Manajemen YKPNMirakhor, Abbas dan Zainal Iqbal. 2007. Pengantar Keuangan Islam: Teori dan Praktik. Terjemahan oleh A.K. Anwar. 2008. Jakarta: Kencana Media GroupMughni, Abdul. 2005. Keuangan Mikro Islam dalam Upaya Pengentasan Masalah Sosial. www.takzia.ac.id, (diaksespada 26 Februari 2017)Muhammad. 2002. Manajemen Bank Syariah. Yogyakarta: UPP AMP YKPNMuhammad. 2004. Manajemen Dana Bank Syariah. Yogyakarta: EkonisiaRedja, George E. 2008. Principles of Risk Management and Insurances. Edisi ke-10. Boston: Pearson International EditionSudarsono, Heri. 2004. Bank dan Lembaga Keuangan Syariah Deskripsi dan Ilustrasi. Yogyakarta: EkonisiaSugiyono. 2015. Pendekatan Kuantitatif, Kualitatif, dan R&D. Cetakan Ke-21. Bandung: AlfabetaSuhendi, Hendi. 2009. Strategi Optimalisasi Peran BMTT sebagai Penggerak Sektor Usaha Mikro. www.fe.unpad.ac.id, (diakses pada 26 Februari 2017)Yin, K Robert. 2002. Studi Kasus (Desain dan Metode). Jakarta: PT. Raja Grafindo PersadaYin, K. Robert. 2009. Case Study Research: Design and Method (4thed.). California: Sage Publications, Inc.Yin, K. Robert. 2013. Studi Kasus (Desain dan Metode). Jakarta: PT. Raja Grafindo Persada